PENGARUH EXPERIENTIAL VALUE TERHADAP BEHAVIORAL INTENTION (Survey terhadap Pengunjung Museum Gedung Sate) - Ulfa Amelinda, - (2020)
The purpose of this study was to determine how the influence of experiential value on behavioural intention at Museum Gedung Sate. The independent variable (X) in this study is experiential value which consists of several sub dimensions, namely visual appeal, entertainment, enjoyment, and escapism and the dependent variable (Y) is behavioral intention. This type of research is descriptive and verification with an explanatory survey method and a cross sectional study approach. The data in this study used primary data with a sample of 160 respondents, namely Visitors of Museum Gedung Sate with a simple random sampling technique. The data analysis technique used is multiple regression with the help of the IBM SPSS for Windows 20.0 program. Visual appeal get the highest ratings. Meanwhile, enjoyment have the lowest score. The results showed that the experiential value variables together and separately had a significant influence on behavioral intention at Museum Gedung Sate.